PENGARUH INFLASI, PDRB DAN KEMISKINAN TERHADAP INVESTASI DI KOTA MAGELANG TAHUN 2006-2018 - M. Ichwan Nur Roshid; Sudati Nur Sarfiah; Panji Kusuma Prasetyanto (Universitas Tidar, 2020)
Investment is one of the main sources to get funds for the City of Magelang, in carrying out activities to encourage economic growth. This investment will result in an increase in output in good development, especially in the City of Magelang. This study uses inflation variables, Gross Regional Domestic Product (GRDP), and poverty on investment in Magelang City in 2006-2018. This study aims to determine whether or not there is an effect of inflation, GRDP and poverty on investment in the City of Magelang in 2006-2018. Investment variable is the dependent variable, while inflation, GRDP and poverty are the independent variables. The method used in this research is quantitative with descriptive approach. This study uses time series data analysis with multiple linear regression analysis models with the OLS (Ordinary Least Square) method. This study aims to determine whether or not there is an influence of inflation, GRDP and poverty variables on investment variables. Partially the results of the study showed that the inflation and GRDP variables had no effect on the investment variable, while the poverty variable had an influence on the investment variables in 2006-2018. While simultaneously the results of the study showed that the variables inflation, GRDP and poverty had an influence on the investment variables in 2006-2018.